1997
DOI: 10.1055/s-2007-979099
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the IGF System and Analysis of the Possible Molecular Mechanisms Leading to IGF-II Overexpression in a Mesothelioma

Abstract: The expression of members of the IGF system in a mesothelioma from a patient suffering from hypoglycemia, in term placenta and HT29 colon adenocarcinoma cells were compared. Very high levels of IGF-II mRNA and protein were detected in the mesothelioma. Moreover, half of the IGF-II protein took the high-molecular-weight form. We also analyzed the parental imprinting status and the promoter usage of the IGF-II gene. Our results showed loss of imprinting (LOI) in the mesothelioma while the imprinting was maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In addition, IGFBP-3 was more overexpressed in MM cell lines and primary tumors than in a nonmalignant mesothelial cell line, 38 despite the report by Hodzic et al showing that IGFBP-3 was downregulated in MM. 34 One explanation for the overexpression of IGFBP-3 in malignancies is that IGFBP-3 may inhibit tumor cell proliferation via a negative feedback mechanism. 37,[39][40][41][42] Another possibility is that unknown defects in IGFBP-3 receptor function may lead to IGFBP-3 overexpression in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IGFBP-3 was more overexpressed in MM cell lines and primary tumors than in a nonmalignant mesothelial cell line, 38 despite the report by Hodzic et al showing that IGFBP-3 was downregulated in MM. 34 One explanation for the overexpression of IGFBP-3 in malignancies is that IGFBP-3 may inhibit tumor cell proliferation via a negative feedback mechanism. 37,[39][40][41][42] Another possibility is that unknown defects in IGFBP-3 receptor function may lead to IGFBP-3 overexpression in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-II gene overexpression is more widespread than first thought and appears to occur in various malignancies, albeit to a variable extent (Hodzic et al 1997, van der Ven et al 1997. Nowadays it is generally accepted that IGF-II is involved in oncogene-induced tumorigenesis (Khandwala et al 2000, Samani et al 2007).…”
Section: Aberrant Igf Expression In Nicthmentioning
confidence: 99%
“…Overexpression of IGF-II in tumours has been mainly attributed to either a loss of imprinting or mutations in tumour suppressor genes (Drummond et al 1992, Christofori et al 1995, Khandwala et al 2000. The mechanisms leading to IGF-II mRNA overexpression in NICTH have rarely been studied (Hodzic et al 1997, Bertherat et al 2000. Hodzic et al (1997) reported loss of imprinting of the IGF-II gene in a mesothelioma causing hypoglycaemia.…”
Section: Aberrant Igf Expression In Nicthmentioning
confidence: 99%
“…Presently, limited information is available regarding mechanisms and clinical relevance of DNA hypomethylation in MPM. For instance, with the exception of a single report of LOI of IGF-II in (58), this phenomenon has not been described in MPM. Similarly, expression of endogenous retroviral sequences has not been evaluated in MPM.…”
Section: Loss Of Imprinting (Loi) and De-repression Of Cg Genesmentioning
confidence: 96%